W. Va. Code ch. 148, § 7 (1870) - (:unkn) unknown (My University, 1870)
Prohibited the habitual conceal carry of any pistol, dirk, Bowie-knife, or weapon of like kind. Violators fined fifty dollars, informants receiving half the fine.
Keywords: CARRY - CONCEALED